Practical security training - Kane, Patrick (Butterworth-Heinemann, 2000)
Practical Security Training is designed to help security departments develop effective security forces from the personnel screening and selection process to ensuring that proper ,cost-efficient training is conducted. Using the building block and progressive method approach allows security staff to become increasingly more effective and more confident. Flexible and practicle, these tools allow security practitioners to adapt them as needed in different environments